High temperature oxidation of rare earth permanent magnets. Part 1 – Microstructure evolution and general mechanism. (1st April 2018) - Firdaus, Muhamad; Rhamdhani, M. Akbar; Rankin, W. John; Pownceby, Mark; Webster, Nathan A.S.; D'Angelo, Anita M.; McGregor, Kathie
Highlights: The microstructure evolution and mechanism of oxidation of (Nd, Pr)FeB magnet at 700–1500 K have been investigated. Three different oxidation microstructure evolutions were observed at 700–1000 K, 1000–1300 K and 1300–1500 K. The different microstructures formed during the oxidation have implications for devising strategies for the recycling/recovery process of (Nd, Pr)FeB magnets. Abstract: The microstructure evolution and mechanism of oxidation of (Nd, Pr)FeB magnet in the range 700–1500 K have been investigated. Bulk (10 × 5 × 5 mm) and powder samples (−150 μm) were oxidized under isothermal and non-isothermal conditions. DSC, XRD, high-temperature XRD, SEM and EPMA characterization techniques were utilized to investigate the general oxidation reactions, microstructure evolutions and phase transformations. Three different microstructure evolutions were observed in the temperature ranges 700–1000 K, 1000–1300 K and 1300–1500 K. The different product microstructures formed during the oxidation have implications for devising strategies for the recycling/recovery process of (Nd, Pr)FeB magnets.